Lacticaseibacillus rhamnosus alleviates intestinal inflammation and promotes microbiota-mediated protection against Salmonella fatal infections - Peng, Xianqi; Ed-Dra, Abdelaziz; Song, Yan; Elbediwi, Mohammed; Nambiar, Reshma B.; Zhou, Xiao; Yue, Min (Frontiers in Immunology, 2022)
The fatal impairment of the intestinal mucosal barrier of chicks caused by Salmonella significantly resulting economic losses in the modern poultry industry. Probiotics are recognized for beneficially influencing host immune responses, promoting maintenance of intestinal epithelial integrity, antagonistic activity against pathogenic microorganisms and health-promoting properties. Some basic studies attest to probiotic capabilities and show that Lacticaseibacillus rhamnosus could protect intestinal mucosa from injury in animals infected with Salmonella Typhimurium. However, the mechanisms underlying its protective effects in chicks are still not fully understood. Here, we used the chick infection model combined with histological, immunological, and molecular approaches to address this question. The results indicated that L. rhamnosus significantly reduced the diarrhea rate and increased the daily weight gain and survival rate of chicks infected with S. Typhimurium. Furthermore, we found that L. rhamnosus markedly improved the immunity of gut mucosa by reducing apoptotic cells, hence effectively inhibiting intestinal inflammation. Notably, pre-treatment chicks with L. rhamnosus balanced the expression of interleukin-1β and interleukin-18, moderated endotoxin and D-lactic acid levels, and expanded tight junction protein levels (Zonula occluden-1 and Claudin-1), enhanced the function of the intestinal mucosal epithelial cells. Additionally, investigations using full-length 16S rRNA sequencing also demonstrated that L. rhamnosus greatly weakened the adhesion of Salmonella, the mainly manifestation is the improvement of the diversity of intestinal microbiota in infected chicks. Collectively, these results showed the application of L. rhamnosus against Salmonella fatal infection by enhancing barrier integrity and the stability of the gut microbiota and reducing inflammation in new hatch chicks, offering new antibiotic alternatives for farming animals.